Keynote: Searching for a New and Better Future of Work - Teevan, Jaime (2022 International ACM SIGIR Conference on Research and Development in Information Retrieval, 2022)
Search engines were one of the first intelligent cloud-based applications that people used to get things done, and they have since become an extremely important productivity tool. This is in part because much of what a person is doing when they search is thinking. Search engines do not merely support that thinking, however, but can also actually shape it. For example, some search results are more likely to spur learning than others and influence a person’s future queries. This means that as information retrieval researchers the new approaches that we develop can actively shape the future of work. The world is now in the middle of the most significant change to work practices in a generation, and it is one that will make search technology even more central to work in the years to come. For the past several millennia, space was the primary technology that people used to get things done. The coming Hybrid Work Era, however, will be shaped by digital technology. The recent rapid shift to remote work significantly accelerated the digital transformation already underway at many companies, and new types of work-related data are now being generated at an unprecedented rate. For example, the use of meeting recordings in Microsoft Stream has more than doubled from March 2020 to February 2022. Knowledge exists in this newly captured data, but figuring out how to make sense of it is overwhelming. The information retrieval community knows how to process large amounts of data, build usable intelligent systems, and learn from behavioral data, and we have a unique opportunity right now to apply this expertise to new corpora and in new scenarios in a meaningful way. In this talk I will give an overview of what research tells us about emerging work practices, and explore how the SIGIR community can build on these findings to help create a new – and better – future of work.